Reversible downregulation of HLA class I in adenoid cystic carcinoma - Xin Gao; Jeffrey Raizer; William C Faquin; Jong Chul Park; Thomas Denize; Ross D Merkin; Annie Li; Bianca L Gonda; Atul K Bhan; Stefan T Kaluziak; Markus D Herrmann; Yu-Chung Huang; et al. (Journal for ImmunoTherapy of Cancer)
Background Adenoid cystic carcinoma (ACC) is a rare, but lethal cancer with low response rates to systemic therapies, such as cytotoxic chemotherapy and immune-checkpoint inhibitors (ICIs). Despite extensive clinical trials, no effective treatments for patients with recurrent or metastatic ACC are available, and ACC mortality rates remain poor.Methods We employed automated multiplex immunofluorescence (mIF), single-cell RNA sequencing (scRNA-seq) Gene Expression analysis, RNA in-situ hybridization, and spatial transcriptomics analysis to characterize the immune landscape of ACC tumors, ACC metastasis, and normal tissues from regions where ACCs arise. Based on results from these studies, we treated freshly resected ACCs with interferon-γ or a stimulator of the interferon genes (STING) agonist in vitro. Additionally, we included one patient with ACC in a phase 1 clinical study of a novel STING agonist (dazostinag) plus pembrolizumab.Results The mIF analysis revealed that ACC tumors are immunologically “cold”, with few tumor-infiltrating T-lymphocytes and low programmed death-ligand 1 (PD-L1) expression. The most striking finding was a very low beta-2-microglobulin (B2M) expression in nearly all ACCs, with only focal expression found in some ACC metastases. mIF and RNA sequencing analyses of normal salivary gland and breast tissues revealed a p63+, NFIB+, basal duct cell population, with similarly low B2M/human leukocyte antigen (HLA) class I expression. Spatial transcriptomics analysis of the focally B2M-positive ACC metastases uncovered the genetic pathway driving upregulation of B2M, an interferon-γ program mediating the reintroduction of HLA-I/B2M; the significantly upregulated genes included IRF1, GBP1, and TAP1. On short-term treatment of primary ACC tissues in vitro with interferon-γ or a STING agonist, we observed strongly upregulated HLA class I/B2M expression. Moreover, treatment of a patient with recurrent, metastatic breast ACC with a STING agonist and pembrolizumab led to a partial response with a 70% tumor reduction.Conclusions Low B2M/HLA class I expression may explain why ACCs are immunologically cold and the lack of response to ICIs. Our findings suggest that the normal cell of ACC origin exists in a B2M/HLA-class I low state, and that pharmacologic manipulation with immune activators, such as STING agonists, can restore HLA/B2M in ACCs, as supported by the promising response observed in a patient with metastatic ACC. These findings indicate a potential path to urgently needed immunotherapies.